Neurological Complications of Tuberculosis in Quetta, Pakistan: Clinical Profile, Outcomes, and Mortality Predictors from a Prospective Cohort Study - Kakar, Amanullah; Nasar, Abdul Bari; Kakar, Ainullah; Ihsan ul Haq; Ahmed, Riaz; Qahir, Muhammad; Muhammad Essa, Muhammad Essa (Indus Journal of Bioscience Research, 2025)
Background: Neurotuberculosis remains a severe manifestation of tuberculosis with high morbidity and mortality, particularly in resource-limited settings. This study aimed to characterize the clinical, diagnostic, and prognostic aspects of neurological complications of tuberculosis at Bolan Medical Complex (BMC), Quetta, Pakistan. Methods: This prospective observational cohort study, conducted from December 2022 to December 2024, enrolled 168 adult patients with microbiologically or histopathologically confirmed neurotuberculosis. Data on demographics, clinical presentation, diagnostic findings (neuroimaging, CSF analysis), treatment, and outcomes were collected. Statistical analysis included descriptive statistics, group comparisons, and Cox Proportional Hazards models to identify mortality predictors. Results: The majority of patients were male (58.3%) and from rural areas (66.7%). Afghan refugees, who made up 22.0% of the population, were 3.1 times more likely to have MDR-TB. In 51.8% of cases, malnutrition increased the risk of death on its own (RR=2.3, p=0.002). With 30.5% of cases presenting at Stage III, tuberculous meningitis (TBM) was the most common consequence (56.5%). The prevalence of MDR-TB was 8.9%, and it was a strong predictor of mortality (aHR=2.6, p=0.009). 53.0% experienced critical treatment delays (>28 days), which increased mortality by 2.4 times (p=0.007). Mortality was highly predicted by hydrocephalus (39.9%) (OR=4.9, p<0.001). At six months, the overall death rate was 23.8%. TBM Stage III (aHR=5.27), MDR-TB (aHR=2.6), treatment delay >28 days (aHR=2.41), and malnutrition (aHR=2.05) were independent predictors of mortality. Mortality was considerably decreased by VP shunting and corticosteroid usage. Conclusion: Malnutrition, MDR-TB, advanced TBM stage, and delayed presentation are important independent indicators of higher mortality among neurotuberculosis patients in Quetta. Improving patient survival and functional results requires timely diagnosis, effective anti-tuberculosis treatment, prudent corticosteroid administration, and surgical intervention.